DRIVERS BEHAVIOR ANALYSIS AND FULFILLMENT OF SIGNS AGAINST TRAFFICK IN PINRANG CITY - Lambang Basri Said Basri Said; Ilham Syafei Syafei; Muhammad Sastera Hasim (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2020)
Traffic is one of the means of community communication that plays a very vital role in facilitating the development that we carry out. The traffic problem is one of the problems on a national scale that develops in tune with the development of society. The problem faced today is the emergence of congestion on various roads, especially at peak hours. Congestion factors are generally caused by the components of facilities, infrastructure, signs and human factors as traffic drivers on the highway. Formulation of the problem, how aspects of the character of the driver, social, economic and cultural aspects of the driver and the fulfillment of traffic markings. Research objectives, to analyze the components of facilities, infrastructure, signs and human factors as drivers. The population of Pinrang City is ± 96,369 people and the number of samples is 100 respondents, the analysis method used is Multiple Linear Regression Software, the results obtained are X5: Aspects of Fulfillment of Signs-Marks 0.334; X4: Rider Culture Aspect 0.313; X1: Character driver coefficient value 0.246; X3: Driver's Economic Aspect,0.075; and X2: Social aspect of the driver, 0.036.